Amino‐Assisted Anchoring of CsPbBr3 Perovskite Quantum Dots on Porous g‐C3N4 for Enhanced Photocatalytic CO2 Reduction. Issue 41 (17th September 2018) - Ou, Man; Tu, Wenguang; Yin, Shengming; Xing, Weinan; Wu, Shuyang; Wang, Haojing; Wan, Shipeng; Zhong, Qin; Xu, Rong
Abstract: Halide perovskite quantum dots (QDs) have great potential in photocatalytic applications if their low charge transportation efficiency and chemical instability can be overcome. To circumvent these obstacles, we anchored CsPbBr3 QDs (CPB) on NH x ‐rich porous g‐C3 N4 nanosheets (PCN) to construct the composite photocatalysts via N−Br chemical bonding. The 20 CPB‐PCN (20 wt % of QDs) photocatalyst exhibits good stability and an outstanding yield of 149 μmol h −1 g −1 in acetonitrile/water for photocatalytic reduction of CO2 to CO under visible light irradiation, which is around 15 times higher than that of CsPbBr3 QDs. This study opens up new possibilities of using halide perovskite QDs for photocatalytic application. Abstract : CsPbBr3 quantum dots were anchored on the polymeric semiconductor g‐C3 N4 porous nanosheets via strong N−Br bond. Chemical bonding cannot only enhance the photocatalytic CO2 reduction performance, but also fix the QDs on a solid surface to improve the stability. This work opens up new possibilities of using halide perovskite QDs for photocatalytic applications.